Food, nutrition and the Afrikaans housewife in Die Huisvrou, 1922-1945 (Historia, 2021)
Within Die Huisvrou, a South African magazine that claims to be one of the first periodicals for Afrikaans women, lie a myriad of curious recipes, nutritional tips and expectations about the relationship between women and food. An examination of the magazine provides evidence of the significant role that food was expected to play in the lives of housewives. These recipes and articles provide a glimpse into what was considered "nutritious" in the period between 1922 and 1945 and the part that food-related activities were supposed to have in women's everyday lives. The contents of Die Huisvrou reveal that women were believed to determine the health of their family with their cooking. They were expected to use food to ensure the health of the family and, by extension, "the nation".